Equity Derivatives - Schofield, Neil C. author. aut Link
XXIII, 487 p. 274 illus.
Keywords: This book provides thorough coverage of the institutional applications of equity derivatives. It starts with an introduction on stock markets' fundamentals before opening the gate on the world of structured products. Delta-one products and options are covered in detail, providing readers with deep understanding of the use of equity derivatives strategies. The book features most of the traded payoffs and structures and covers all practical aspects of pricing and hedging. The treatment of risks is performed in a very intuitive fashion and provides the reader with a great overview of how dealers approach such derivatives. The author also delivers various common sensical reasons on which models to use and when. By discussing equity derivatives in a practical, non–mathematical and highly intuitive setting, this book enables practitioners to fully understand and correctly structure, price and hedge these products effectively, and stand strong as the only book in its class to makethese equity-related concepts truly accessible.